Complete mitochondrial genome and phylogenetic analysis of the Gray's pipefish Halicampus grayi Kaup 1856. Issue 2 (3rd July 2019) - Chen, Jianzhen; Lai, Mengru; Sun, Siya; Zhang, Guangji; Ge, Yuqing; Cheng, Rubin
Abstract: In the present study, the complete mitochondrial genome of H. grayi was determined and annotated. The circular mitogenome is 16, 959 bp in length and contains 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and a control region. Most of the PCGs start with ATG, but CO1 begins with a GTG start codon. Phylogenetic analysis revealed that H. grayi was strictly related to network pipefish Corythoichthys flavofasciatus with 100% bootstrap support value. This work provides basic molecular information that would be useful for further investigation on conservation genetics and evolutionary relationships of H. grayi .